2014
DOI: 10.1007/s11552-014-9725-8
|View full text |Cite
|
Sign up to set email alerts
|

Distal Ulna Leiomyosarcoma Treated with Custom Polymethylmethacrylate Prosthesis with a 4-Year Follow-up

Abstract: Custom methacrylate in situ radioulnar joint prosthesis for reconstruction of a large segment of the distal ulna can be a valid option to reestablish the mechanical continuity of the forearm, reducing pain and improving strength and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…results and patient satisfaction of three patients with Madelung's deformity with a follow-up time of 2 years. Pacheco-Nuñez et al 13 suggested that a custom-made implant can be used to reconstruct the DRUJ after resection of the distal ulna due to a tumor and reported promising results in one case with a follow-up time of 4 years. On the contrary, Cooney et al 14 suggested that the reconstruction of the DRUJ is not required after the removal of a tumor in the distal end of the ulna to maintain wrist function, which is in line with the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…results and patient satisfaction of three patients with Madelung's deformity with a follow-up time of 2 years. Pacheco-Nuñez et al 13 suggested that a custom-made implant can be used to reconstruct the DRUJ after resection of the distal ulna due to a tumor and reported promising results in one case with a follow-up time of 4 years. On the contrary, Cooney et al 14 suggested that the reconstruction of the DRUJ is not required after the removal of a tumor in the distal end of the ulna to maintain wrist function, which is in line with the findings in this study.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the literature is scarce regarding the management of complications related to the Aptis implant in wrists with more rare conditions, such as rheumatoid arthritis, congenital malformations, or tumors in the distal end of the ulna. 13,14 To this end, this study aims to describe the clinical results, management of remarkable complications, patient satisfaction regarding revision surgery, and the esthetic appearance of the wrist in this specific cohort.…”
mentioning
confidence: 99%